2008
DOI: 10.1175/2008jcli2109.1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Northern Australian Rainy Season

Abstract: A trend of increasing rainfall over much of north and northwest Australia over recent decades has contrasted with decreases over much of the rest of the continent. The increases have occurred during the summer months when the rainy season is dominated by the Australian monsoon but is also affected by other events such as tropical cyclones, Madden-Julian oscillations, and sporadic thunderstorms. The problem of diagnosing these trends is considered in terms of changes in the timing of the rainy season. While num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 27 publications
2
68
0
Order By: Relevance
“…The accumulated annual rainfall is calculated from July of the previous year to June of the next year. The result shown here is consistent with the rainy window adopted by Smith et al (2008), from 1 September to 30 April. This simple estimate is satisfactory for our purposes, because we are not interested in the actual dates of the monsoon, but rather in the difference between the start and end of the rainy season during the composited Modoki years compared to the climatology.…”
Section: The Australian Monsoon Response To Modoki Eventssupporting
confidence: 91%
See 3 more Smart Citations
“…The accumulated annual rainfall is calculated from July of the previous year to June of the next year. The result shown here is consistent with the rainy window adopted by Smith et al (2008), from 1 September to 30 April. This simple estimate is satisfactory for our purposes, because we are not interested in the actual dates of the monsoon, but rather in the difference between the start and end of the rainy season during the composited Modoki years compared to the climatology.…”
Section: The Australian Monsoon Response To Modoki Eventssupporting
confidence: 91%
“…2. Smith et al (2008) also showed a shorter rainy season for northern Australia with traditional El Niñ o events.…”
Section: The Australian Monsoon Response To Modoki Eventsmentioning
confidence: 90%
See 2 more Smart Citations
“…The MEP and ST(DEP) represented the climatological mean of EP and standard deviation of DEP for each calendar day, respectively. The base period for calculating MEP and ST(DEP) needs to be at least 30 years ) so we used 1971-2000, which is a common period used for analysis of Australian climate (Smith et al, 2008). During the computation process, if DEP continued to be negative for more than 2 days, the duration of summation D was increased by the number of days for which the DEP was negative which had no upper limit.…”
Section: Calculation Of the Effective Drought Indexmentioning
confidence: 99%